Religious Tolerance And Communication Dynamics In Educational Environments - Salwa, Salwa; Rahmawati, Endang; Suhadah, Suhadah; Saudi, Yusron (KOMUNIKA, 2024)
Interpersonal communication between students and lecturers plays an important role in increasing learning motivation both on and off campus. Effective communication is essential to support smooth academic interaction. Meanwhile, religious tolerance encourages individuals to socialize not only with those of the same faith but also with those of different beliefs, thereby creating a harmonious environment. This study aims to explore the dynamics of interpersonal communication and religious tolerance between students and lecturers in an academic setting. This study employed a qualitative method with a phenomenological approach, involving 99 respondents. Data were collected through questionnaires and analyzed using the Miles and Huberman model. The results showed several indicators of interpersonal communication, including openness (25%), empathy (31%), support (33%), a positive attitude (32%), and equality (34%). Indicators of religious tolerance included care (38%), compassion (38%), mutual respect (40%), openness (44%), and comfort (36%). The average scores for interpersonal communication and religious tolerance were 31% and 39%, respectively. These findings indicate a positive pattern of communication in the academic environment and a fairly good level of tolerance among students and lecturers. The results provide a foundation for designing training programs that strengthen interpersonal communication skills and promote religious tolerance in higher education institutions.